The State and Necessity of Standardization of State Financial Control in Ukraine (Economic journal of Lesya Ukrainka Volyn National University, 2016)
One of key problems of functioning of state financial control for today is absence of the unique compatible standards of realization the organs of SFC of their powers: every organ develops and uses own positions and instructions, which do not have system intercommunication, are narrow after an application domain and does not take into account the requirements of legislative and normatively-legal acts. It results in chaoticness, inconsistency and inconsistence of activity of organs of SFC, expense of considerable money on their financing, does impossible comparison of job and her estimation executed by them performances. Undertaken a study grounded, that deciding this problem is possible by means of standardization of state financial control, that will provide the row of positive changes: co-ordination and intercommunication between the organs of SFC in the process of implementation of their plenary powers, only methodology of opening of violations and abuses, compared and only going near the estimation of results of their activity, functioning of only infobase of organs of SFC etc. However, the process of standardization requires realization of row of events, in particular: legislative, institutional and organizational character, strengthening of positions of all organs of SFC, intercommunication of developers of standards with the direct performers of control-revision and expertly-analytical events.
Keywords: state financial control, International standards of supreme bodies of audit (ISSAI), organs of state financial control, standards of state financial control, standardization of state financial control